The relationship between household chaos and child, parent, and family outcomes: a systematic scoping review - Samantha Marsh; Rosie Dobson; Ralph Maddison (BMC, 2020)
Abstract Background Household chaos, represented by the level of disorganisation or environmental confusion in the home, has been associated with a range of adverse child and family outcomes. This review aims to (1) identify how household chaos is measured, (2) chart study details of household chaos literature, and (3) map the existing literature with respect to the relationship between household chaos and child, parent, and family outcomes. We expect that this review will highlight the need to consider the importance of household chaos in child well-being research, particularly in those families where children may be more vulnerable to the adverse effects of household chaos. Methods We searched five electronic databases (last updated September 1st 2018) in addition to Google Scholar, and identified publications via a 3-stage screening process, which was conducted by two researchers. Published studies were included if they investigated the association between household chaos and child, parent, or family outcomes. Research that investigated household chaos as a mediator or moderator, or that investigated how the relationship between household chaos and the outcome of interest was mediated or moderated, were also included. Results One hundred twelve studies in 111 publications were included. The majority were conducted in the United States (n = 71), and used either cross-sectional (n = 60) or longitudinal (n = 49) study designs. Outcomes of interest were categorised into seven categories: (1) cognitive and academic (n = 16), (2) socio-emotional and behavioural (n = 60), (3) communication (n = 6), (4) parenting, family, and household functioning (n = 21), (5) parent outcomes (n = 6), (6) hormone (n = 8), and (7) physical health and health behaviours (n = 19). There was consistent evidence for significant correlations between household chaos and adverse outcomes across all seven categories in diverse populations with respect to age, disease status, and socio-economic status (SES). Conclusion There is consistent evidence for associations between household chaos and a number of adverse child, parent, and family-level outcomes. Household chaos may also help describe variations in outcomes between low SES and child development.